The influence of electrical high-speed rotation on mandibular third molar surgeries: a prospective, randomized, split-mouth clinical and radiographic study - Sol, Izabella [UNESP]; Tonini, Karen Rawen [UNESP]; dos Reis, Karen Santin [UNESP]; Hadad, Henrique [UNESP]; Ponzoni, Daniela [UNESP] (Springer Nature, 2024)
The aim of this split-mouth randomized clinical trial was to evaluate the clinical outcomes (operative time, edema, trismus, and pain), the immediate histological effects, the alveolar repair (2 and 4 months), and the quality of life after the extraction of impacted third molars using high-speed pneumatic and electrical rotation. Sixteen patients underwent extraction of the two mandibular third molars with a minimum interval of 15 days. On one side of the participant’s mouth, high-speed pneumatic rotation was used (Control Group—CG) while for the other side, high-speed electrical rotation was used (Study Group—SG). Statistical analysis included ANOVA repeated measures and Pearson correlations. SG group showed: shorter operative time (p = 0.019), less pain (p = 0.034), swelling (p < 0.001) and trismus (p = 0.025) on the 1st postoperative day; less pain (p = 0.034) and trismus (p = 0.010) on the 3rd postoperative day; less trismus (p = 0.032) on the 7th postoperative day; and better quality of life (p = 0.007). No differences were observed for peripheral bone damage or bone density of alveolar repair at 2 and 4 months between groups. Electric high-speed rotation provided better postoperative clinical parameters of pain, edema and trismus when compared with pneumatic high-speed rotation for mandibular third molar surgery. Trial registration: Brazilian Registry of Clinical Trials registration number RBR-4xyqhqm (https://ensaiosclinicos.gov.br/rg/RBR-4xyqhqm).
Keywords: Bone regeneration; Molar, third; Oral surgical procedures; Osteotomy; Tooth extraction